ANALISA KEHANDALAN JARINGAN INTERNET DENGAN PENDEKATAN QUALITY OF SERVICE PADA R.S KUSTA DR. RIVAI ABDULLAH PALEMBANG - Wijaya, Alek; Rasmila, Rasmila (JURNAL ILMIAH MATRIK, 2018)
Kusta Dr.Rivai Abdullah Palembang Hospital is an agency that moves in the field of health. Hospital Kusta Dr. Rivai Abdullah Palembang is one of the health agencies that utilize internet network to perform data management activities such as LPSE, BPJS, and E_Pilink information systems that connect directly to the ministry of health and taxation. Quality of Service (QOS) is used to measure the level of Internet network connection performance which aims to improve the quality of internet service for the Hospital. The method used is action reseach that is action method that aims at theory and practice can be integrated with learning and usage of measurement using Axence NetTools5 which is used to know factors that can affect Quality of Service (QOS) network that is damping, distortion, noise and bandwidth capacity. The parameters used in Quality of Service (QOS) include throughput, packet loss, delay and bandwidth. Results of evaluation after diagnosis of the formulation of the problem in order to maximize the performance of Internet network Hospital Kusta Dr. Rivai Abdullah Palembang, which is intended for data management activities to be better and efficient. Keywords:Quality of Service (QoS) Parameters, Action Reseach, Axence NetTools.